2017
DOI: 10.4236/jss.2017.59013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of E-Service Quality through Customer Satisfaction (a Case Study of FBR E-Taxation)

Abstract: This study developed the research model to analyze the relationship between suggested service quality dimensions with customer satisfaction and customer reuse intention. The sample count of 188 from FBR's e-taxation/e-filling users was used to examine the study model. In this study, the Exploratory factor analysis EFA used to observe the validity and reliability of the measurement model. The statistical method i.e. regression model has been used to check the research model significance relationship among vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…by contacting customers directly through online communications rather than sending auto-replies (Madu & Madu, 2002). Taking customers into account is also considered a type of empathy (Ali et al, 2017). and Zhang and Prybutok (2005) concluded that empathy was a critical e-service quality factor to satisfy customers.…”
Section: Empathymentioning
confidence: 99%
See 2 more Smart Citations
“…by contacting customers directly through online communications rather than sending auto-replies (Madu & Madu, 2002). Taking customers into account is also considered a type of empathy (Ali et al, 2017). and Zhang and Prybutok (2005) concluded that empathy was a critical e-service quality factor to satisfy customers.…”
Section: Empathymentioning
confidence: 99%
“…Empathy also has a positive correlation with M-customer satisfaction (Aghdaie & Faghani, 2012). On the other hand, Ali et al (2017) eliminated the empathy from e-service quality because all empathy's decimation were placed under 0.5 in factor analysis test , and both Hussein and El Aziz (2013) and Ladhari (2010) found that empathy was less critical in the case of online portals. Indeed, Ali (2017) went so far as to eliminate empathy from the e-service quality factors investigated in his study.…”
Section: Empathymentioning
confidence: 99%
See 1 more Smart Citation
“…Berdasarkan gambar dan tabel diatas bahwa Kualitas Layanan (X2) terhadap Kepuasan Pengguna (Y) berpengaruh signifikan, dikarena nilai T-Statistic > 1,96, hasil penelitian ini didukung oleh penelitian terdahulu oleh Wodward (2017), Kim (2015), Ratanavahara (2016), Ibrahim (2016), dan Ali (2017) yang menyatakan bahwa, Kualitas Layanan (X2) berpengaruh signifikan terhadap Kepuasan Pengguna (Y). karena kulitas layanan terhadap kepuasan pengguna itu sangat penting bagi perusahaan jasa seperti traveloka, layanan yang mempermudahkan konsumen dalam menggunakan jasa pemesanan tiket pesawat ini dapat membuat konsumen merasa puas karena memudahkan konsumen dalam menggunakan jasa tersebut selain mudah, cepat dan praktis untuk jasa pemesanan tiket pesawat.…”
Section: Pembahasan Hipotesis H3unclassified
“…It is also considered highly influential on the online purchasing decisions where its existence can make online services attractive and effective so that it helps the marketplaces to obtain high purchasing decisions from the consumers (Rozi & Harti, 2017). Previous researches related to e-service quality have focused on customer satisfaction (Bressolles et al, 2014;Finn, 2011;Ali et al, 2017;Ma̳ Sabiote et al, 2012;Zavareh et al, 2012), consumer loyalty (Yen & Lu, 2008), and both of them (Al-dweeri et al, 2017;Chang et al, 2009;Ghane et al, 2011;Sheng & Liu, 2010). Based on the gaps in the previous research results and the phenomena explained earlier, it is essential to study the online purchasing decision and the factors influencing them, including the ease of transaction and e-service quality.…”
Section: Introductionmentioning
confidence: 99%